KNOWLEDGE AND PERCEPTION OF MOTHERS REGARDING CHILD IMMUNIZATION IN A TERTIARY CARE HOSPITAL PUNJAB, PAKISTAN - YASMEEN , S; NAWAZ , R; BASHIR , S (Biological and Clinical Sciences Research Journal, 2023)
Child immunization stands out amongst the best intelligent divulgences at any point. It shields adolescents from becoming sick and dead from appalling diseases, diminishing the pain of various guardians. In this study, a quantitative cross-sectional study design is used. The self-administered questionnaire is used to measure the knowledge and perception of mothers regarding child immunization. The data was analyzed using SPSS version 18 and Microsoft Excel. Regarding sources of knowledge, 70% of mothers responded that they got information about the immunization of their child from a Health worker in their town, 2% of mothers responded that they had got information through mass media, i.e., television, social media, etc., out of 100 participants 8% asked that they got information regarding the immunization of their child through the neighborhood, and 20% mothers asked that they got information about immunization from nearest hospital/ health care setup. This study concluded that most of the immunization information is given by Health workers, and mothers perceived that the vaccination is important for their children, but few of them perceived immunization as ineffective.